On the association between Chinese EFL teachers’ academic buoyancy, self-efficacy, and burnout - Ding, Jie; He, Li (Frontiers in Psychology, 2022)
Buoyant and high self-efficacious teachers seem to be unlikely to feel burned out. Accordingly, examining the relationship between teachers’ buoyancy and self-efficacy seems significant. Even though the correlation between self-efficacy and burnout has been studied, precise attention should be paid to the quantitative investigations of the relationship between teachers' academic buoyancy, self-efficacy, and burnout in China, English as a Foreign Language(EFL) context. To address this gap, the present study aimed to assess the relationship between Chinese EFL teachers’ academic buoyancy, self-efficacy, and burnout. In doing so, 399 Chinese EFL teachers (354 females and 45 males) were selected from 11 provinces and 18 cities in China. Three related questionnaires were virtually distributed among participants to gather data. The correlational tests revealed significant negative associations between Chinese EFL teachers' burnout, self-efficacy, and academic buoyancy. The outcomes of multiple regression analyses also indicated that teachers’ burnout was negatively predicted by their self-efficacy and academic buoyancy. Finally, The implications of the results are discussed.